Gradsko poglavarstvo Varaždin u međuratnom razdoblju (1918.-1941.) - Tuk, Ana (2021)
Članak razmatra ustroj, djelokrug i teritorijalnu nadležnost Gradskoga poglavarstva Varaždin između dva svjetska rata. Prikazana su tri međusobno koordinirana tijela Gradskoga poglavarstva: gradsko zastupstvo kao lokalno predstavničko tijelo, odbori kao savjetodavna tijela zastupstva i gradsko poglavarstvo kao izvršno tijelo. U poglavlju o zastupstvu kronološki su predstavljeni svi mandati zastupstva, načelnici i vladini povjerenici koji su upravljali gradom. U narednom poglavlju razrađen je djelokrug svakoga odbora zasebno i taksativno su pobrojani svi odbori izabrani u promatranom razdoblju. Posljednje poglavlje analizira organizaciju ustrojbenih jedinica u kojima se je odvijalo poslovno djelovanje poglavarstva. Pogled na djelovanje gradske uprave zaokružen je zakonskom regulativom i naznakom unitarističko-centralističkih i apsolutističkih tendencija koje su oblikovale svekoliku društveno-političku zbilju, uključujući i rad jedinica lokalne vlasti.
The article analyzes the structure, scope and territorial jurisdiction of the Varaždin City Government, a unit of local administration that governed the Varaždin municipality in the period 1918-1941. From 1918 to 1920, the city municipality included the area of the city of Varaždin together with the villages of Varaždin Breg and Novo Selo, and from January 1, 1921 it was further expanded with the village of Šandorovec.Two basic laws defined the structure and scope of city governments between the two world wars: the Law on the Organization of City Municipalities in the Kingdoms of Croatia and Slavonia of 1895 and the Law on City Municipalities of 1934. After the introduction of the dictatorship in 1929, two more laws were passed that had a decisive impact on the functioning of cities. One dissolved all self-governments on the territory of the state and the other annulled all existing election procedures, so that all subsequent city councils were appointed by a Ban"s decision. The abolition of previous legislation, strict hierarchical supervision, the appointment of city councils and government commissioners close to the state regime and the complete denial of electoral principles led, especially in the first half of the 1930s, to the narrowing of self-governing rights of city municipalities. The paper presents three mutually coordinated bodies of the City Government: the council as a local representative body, committees as advisory bodies of the council and the government as an executive body. The chapter on the city council, in addition to the structure and competencies, provides a chronological overview of the mandate of the council and a list of mayors and government commissioners who changed during the interwar years. In the 1920s, four city councils were elected and from 1929 to 1941, five were appointed.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 214-216.
Sažetak ; Summary.
Keywords: Gradsko poglavarstvo -- Gradska uprava -- Upravna povijest -- Načelnik; Varaždin